2012
DOI: 10.1029/2012jd018304
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends in nitrogen oxide emissions from motor vehicles at national, state, and air basin scales

Abstract: [1] A fuel-based approach is used to estimate nitrogen oxides (NO x = NO + NO 2 ) emissions from gasoline-and diesel-powered motor vehicles. Estimates are made at the national level for the period 1990-2010. Vehicle emissions are also estimated at the state level for California, and for the South Coast (Los Angeles) and San Joaquin Valley air basins. Fuel-based emission estimates are compared with predictions from widely used emission inventory models. Changes in diesel NO x emissions vary over time: increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(214 citation statements)
references
References 29 publications
10
203
1
Order By: Relevance
“…For example, Fujita et al (2012) found that mobile source NO x emissions from the MOVES model overestimated NO x emissions that had been determined from measurements made in a highway tunnel. A fuel-based emission inventory by McDonald et al (2012) yielded relatively constant on-road mobile source NO x emissions from 1990 to 2000 (compared with a 12% reduction in EPA's trend inventory), but comparable (within 7%) mobile source NO x emissions in 1999 and 2008. Xing et al (2013) report national NO x emissions of~28 mT in 1990 and~14 mT in 2010, compared with EPA's trends inventory of 26 mT and 15 mT in 1990 and 2010, respectively, as shown in Table 1; total NO x emission reductions between 1990 and 2010 are 48% according to Xing et al (2013) and 42% according to EPA (2015d).…”
Section: Precursor Emissionsmentioning
confidence: 99%
“…For example, Fujita et al (2012) found that mobile source NO x emissions from the MOVES model overestimated NO x emissions that had been determined from measurements made in a highway tunnel. A fuel-based emission inventory by McDonald et al (2012) yielded relatively constant on-road mobile source NO x emissions from 1990 to 2000 (compared with a 12% reduction in EPA's trend inventory), but comparable (within 7%) mobile source NO x emissions in 1999 and 2008. Xing et al (2013) report national NO x emissions of~28 mT in 1990 and~14 mT in 2010, compared with EPA's trends inventory of 26 mT and 15 mT in 1990 and 2010, respectively, as shown in Table 1; total NO x emission reductions between 1990 and 2010 are 48% according to Xing et al (2013) and 42% according to EPA (2015d).…”
Section: Precursor Emissionsmentioning
confidence: 99%
“…Likewise, NO x decreases in Bakersfield have been observed (from space) at approximately the same rate . NO x controls on heavy-duty diesel trucks that are in the implementation phase (McDonald et al, 2012) will reduce NO x emissions without concomitant VOC decreases and bring about the −50 % NO x scenario relatively quickly. Figure 7 shows the absolute P O 3 (ppb h −1 ) and percentage changes calculated during CalNex (black) on weekdays (solid line) and weekends (dashed line) for the three scenarios.…”
Section: Ozone Production Rates and The Impacts Of Emissions Controlsmentioning
confidence: 99%
“…We present an analysis to identify driving chemical mechanisms and to quantify the effects of large reductions in nitrogen oxides (NO x ) (e.g., Russell et al, 2012;McDonald et al, 2012) on secondary aerosol chemistry. We take advantage of decreased NO x emissions on weekends compared to weekdays, which occur mostly without changes in other gas-phase emissions (e.g., Dallmann et al, 2012), and couple these weekday-weekend patterns to long-term NO x reductions .…”
mentioning
confidence: 99%